2003
DOI: 10.1136/jmg.40.12.913
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation in a patient with insulin-like growth factor 1 (IGF1) deficiency

Abstract: T he insulin-like growth factors (IGFs; somatomedins) comprise a family of peptides that play important roles in mammalian growth and development. The principal members of this family are IGF1 and IGF2. IGF1 (somatomedin C), a 70 residue basic polypeptide, mediates many of the growth promoting actions of growth hormone (GH) and has metabolic and mitogenic effects.1 The major source of circulating IGF1 is the liver, but it is also produced in a wide variety of tissues and has endocrine and paracrine modes of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
0
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(119 citation statements)
references
References 17 publications
3
109
0
7
Order By: Relevance
“…Audiograms of the three patients with complete IGF-I deficiency due to a homozygous deletion or mutation of the IGF-I gene demonstrate severe bilateral sensorineural deafness (13)(14)(15). This is confirmed by absent brainstem evoked potentials in one of the patients (14).…”
Section: Hearingmentioning
confidence: 70%
See 1 more Smart Citation
“…Audiograms of the three patients with complete IGF-I deficiency due to a homozygous deletion or mutation of the IGF-I gene demonstrate severe bilateral sensorineural deafness (13)(14)(15). This is confirmed by absent brainstem evoked potentials in one of the patients (14).…”
Section: Hearingmentioning
confidence: 70%
“…In contrast, an IGF-I gene deletion or mutation results in severe intrauterine growth retardation as is demonstrated in the patient described by Woods et (K4 and K6.5 SDS respectively) (13)(14)(15). The finding that genetically determined low IGF-I levels, due to polymorphisms in the IGF-I promoter region, result in a reduced birth weight and length support the role of IGF-I in fetal growth (16,17).…”
Section: Intrauterine Growthmentioning
confidence: 81%
“…The severity of the foetal growth restriction is illustrated with birth weight standard deviation scores (SDS) ranging from −2.5 to −3.5 (Table 1) 36, 37, 38, 39, 40.…”
Section: Organ‐specific Roles Of Igf‐1 In the Foetusmentioning
confidence: 99%
“…(1)(2)(3)11) A role of IGF-1 in bone metabolism is supported by the fact that patients with IGF deficiency as a result of IGF1 gene deletion or inactivating mutation display osteopenia. (12)(13)(14) The association between serum IGF-1 and BMD has been evaluated in several cohorts but with conflicting results. (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) A positive association has been reported in some studies, (15,17,(20)(21)(22)(23)25,26) whereas no association has been found in other studies.…”
Section: Introductionmentioning
confidence: 99%